Pengaruh Negosiasi Budaya Pada Pertunjukan Musik Gamelan Soepra Terhadap Generasi Centennial - Yosaphat Yogi Tegar Nugroho; Ekawati Marhaenny Dukut (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2022)
Gamelan is the work of adiluhung from the Indonesian nation, and is synonymous with Javanese society. In its development, Javanese Gamelan began to be degraded by global culture. Centennial generation children are considered more interested in pop music than their own cultural output, such as Javanese Gamelan. Henricus Constant Van Deinse, SJ in 1957 had an interest in Javanese gamelan, and innovated to modify the tone shape of gamelan by combining it with Western musical instruments so that it could attract the attention of the younger generation. When Van Deinse's gamelan was staged at an event in Senayan, it happened that Indonesian president Ir. Soekarno was present at the event, and was named Gamelan Soepra (Soegijapranata) in 1965. This is in accordance with the origin of the gamelan from Central Java and its famous hero is Mgr. Soegijapranata. This study aims to examine Gamelan Soepra in the perspective of hybrid culture theory. This research uses a qualitative approach, and the method used is purposive sampling by directly appointing informants who are considered gamelan experts. The result of this study is to know the philosophy and ensemble format of Javanese gamelan, as well as cultural hybrid products in the form of soepra gamelan, and its influence on the centennial (Z) generation.